Fetal Growth Cut-Off Point To Predict Neonatal Outcome In Pregnancy With Normal And Deficient Vitamin D Levels: Intergrowth-21, World Health Organization Fetal Growth Curve, And Hadlock’s Estimated Fetal Weight - Dewantiningrum, Julian; Kristanto, Herman; Pudjonarko, Dwi; Mexitalia, Maria; Ediati, Annastasia; Soejoenoes, Ariawan; Hadisaputro, Suharyo (RSUP Dr. Kariadi, 2023)
Purpose : Analyze the cut-off point of fetal growth based on the Intergrowth-21, World Health Organization (WHO), and Hadlock’s estimated fetal weight (EFW) in pregnant women with normal or deficient vitamin D levels to predict neonatal outcomes. Method: This cross sectional study to develop a diagnostic test, included 120 of pregnant women who completed follow up until children aged 2 years, divided into normal and deficient vitamin D group. Ultrasound and maternal vitamin D level examined during the second trimester of pregnancy. EFW was calculated using Hadlock’s formula and plotted on the Intergrowth-21 and WHO curves. The reference standards were the neonatal outcome, LBW, stunting, and neurocognitive impairment. Significant odds ratio (OR) value and area under the curve (AUC) of 0.6 are used to determine the cut-off point to be used. Result: Fetal growth curve was based on the WHO at the 5th percentile to predict LBW to have an AUC of 0.6 and OR of 6, 95% confidence interval (CI) of 1.36–26.45. The AUC for predicting LBW based on Intergrowth and Hadlock were 0.45 and OR not significant. As well as the AUC estimated stunting based on Hadlock, the Intergrowth-21 and the WHO fetal growth curves is <0.6 with OR not statistically significant. The AUC predicted neurocognitive impairment based on WHO’s chart was 0.6 but OR not statistically significant. Conclusion: The WHO fetal growth curve can be used to predict LBW. The cut-off point of the fetal growth curve and which percentile is determined by the neonatal outcome.